2014
DOI: 10.1007/s11605-014-2628-8
|View full text |Cite
|
Sign up to set email alerts
|

A Pedunculated Giant Esophageal Liposarcoma: a Case Report and Literature Review

Abstract: Esophageal liposarcoma is an extremely rare tumor. The majority of patients are males; dysphagia is the most common initial symptom, and preoperative biopsy is unreliable. Because these tumors are pedunculated, well-circumscribed, and well-differentiated, they can be safely resected locally. All patients need long-term follow-up as this disease can recur many decades after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Primary esophageal liposarcomas are rare, with only 42 cases being reported in English-language literature as of August 2016[1]. Histologically, liposarcomas can be further classified into 4 subtypes based on their degree of differentiation: Dedifferentiated, well-differentiated, myxoid, or pleomorphic[2].…”
Section: Introductionmentioning
confidence: 99%
“…Primary esophageal liposarcomas are rare, with only 42 cases being reported in English-language literature as of August 2016[1]. Histologically, liposarcomas can be further classified into 4 subtypes based on their degree of differentiation: Dedifferentiated, well-differentiated, myxoid, or pleomorphic[2].…”
Section: Introductionmentioning
confidence: 99%
“…A giant thoracic neoplasm is extremely rare and has only occasionally been cited in the literature, usually in single cases . To our knowledge, only one previous has reported conclusions after surgical treatment .…”
Section: Discussionmentioning
confidence: 94%
“…A giant thoracic neoplasm is extremely rare and has only occasionally been cited in the literature, usually in single cases. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] To our knowledge, only one previous has reported conclusions after surgical treatment. 26 Our retrospective study of 45 patients showed the complexity and heterogeneity of giant thoracic neoplasm through clinical characteristics, imaging manifestations, surgical management, pathology, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Background: Liposarcomas are rare mesenchymal malignancies. Oesophageal liposarcomas (OLSs) are extremely rare, with approximately 40 cases reported in the medical literature[ 99 ]. OLSs seem to occur preferably in middle-aged to elderly male patients[ 99 ].…”
Section: Rare Primitive Oesophageal Malignant Tumours Of Non-epithelimentioning
confidence: 99%
“…Oesophageal liposarcomas (OLSs) are extremely rare, with approximately 40 cases reported in the medical literature[ 99 ]. OLSs seem to occur preferably in middle-aged to elderly male patients[ 99 ]. OLSs can be classified into three subtypes: (1) Well-differentiated and dedifferentiated liposarcoma (WDLS/DDLS); (2) Myxoid liposarcoma (MLS); and (3) Pleomorphic liposarcoma (PLS)[ 100 ].…”
Section: Rare Primitive Oesophageal Malignant Tumours Of Non-epithelimentioning
confidence: 99%